Reduced inhibition in brainstem circuits in classical trigeminal neuralgia. (13th August 2018) - Gündüz, A.; Uygunoğlu, U.; Uluduz, D.; Saip, S.; Siva, A.; Göksan, B.; Kızıltan, M.E.
Abstract: Objective: We hypothesized that prepulse modulation (PPM) would be altered in trigeminal neuralgia (TN) if suprasegmental inhibitory network involvement was present and tested our hypothesis in a group of patients with classical TN. Methods: The study enrolled nine consecutive patients with classical TN and 14 healthy subjects. Diagnosis and classification followed the International Classification of Headache Disorders‐third edition (beta version). The blink reflex (BR) and BR‐PPM were recorded. Ipsilateral recordings were made after stimulating each trigeminal nerve in the patient group whereas right‐sided recordings were performed after stimulating the right trigeminal nerve in the healthy subjects. A conditioning electrical stimulus was applied to the ipsilateral median nerve at interstimulus intervals (ISIs) of 50 and 100 ms before the test stimulus to the supraorbital nerve. Results: The unconditioned BR recordings were similar in all groups. In the healthy subjects, the prepulse stimulus resulted in a reduced R2 magnitude ( p  = 0.000, Friedman's test) and longer R2 latency ( p  = 0.008, Friedman's test) at ISIs of 50 and 100 ms in comparison with unconditioned recordings. The R2 latency differed significantly between the unconditioned recordings and the ISI of 100 ms. In the patients with TN, no significant change was observed on either the symptomatic or asymptomatic sides. Conclusions: There is a bilateral prepulse inhibition deficit in TN, even on the asymptomatic side. Our findings provide electrophysiological evidence for suprasegmental changes and loss of filtering activity at the brainstem in level TN.